DARI KEBIJAKAN KE PRAKTIK: MEMPERKUAT KAPASITAS GURU SEKOLAH DASAR UNTUK PEMBELAJARAN MENDALAM MELALUI PENGABDIAN MASYARAKAT - Bachtiar, Bachtiar; Ramdhani, Sendi; Sylvia, Sylvia (Universitas Mataram, 2025)
Contemporary perspectives on 21st-century education emphasize that primary schooling must cultivate transferable competencies that extend beyond content mastery. In Indonesia, the implementation of the 2023 Curriculum and the Merdeka Belajar framework foregrounds Deep Learning (Pembelajaran Mendalam) as a means to achieve the 6Cs (i.e., character, citizenship, collaboration, communication, creativity, and critical thinking) from the earliest grades. This study reports a community service (Pengabdian Kepada Masyarakat, PKM) intervention designed to strengthen primary teachers’ capacity to understand and implement this policy in their classrooms. The program involved 28 teachers from SD Negeri Pondok Cabe Ilir 02, Tangerang Selatan, and adopted a four-stage model: observation, socialization, workshop and mentoring, and evaluation. A mixed-methods approach was employed, incorporating teacher surveys on knowledge and self-efficacy, classroom observations aligned with the 6Cs, analysis of lesson plans and student artifacts, and focus group discussions. Data were analyzed using descriptive statistics, inferential tests, and thematic analysis. The findings reveal significant improvements in teachers’ knowledge, understanding, and awareness of Deep Learning, which fostered a collective commitment to redesign lessons and adopt more active, student-centered pedagogies. Teachers applied differentiated strategies across grade levels: story- and play-based learning in lower grades, and guided inquiry in both middle and upper grades. The program also encouraged professional collaboration and mentoring, although barriers such as limited preparation time, insufficient resources, and varied levels of teacher readiness persisted. These results suggest that the implementation of Deep Learning in primary schools requires sustained and context-sensitive professional development, supportive school leadership, adequate resources, and longitudinal research to link changes in teacher practice with long-term improvements in student learning outcomes.